Pandangan Positif Matematika terhadap Internalisasi Nilai “Performance Character” dalam Pembelajaran Matematika Sekolah Dasar - Sabaruddin Dahlan Husen; Rosnidar Mansor (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2019)
This article has a purpose to discuss about character building for students in elementary level by developing positive attitude and positive opinion towards mathematics. Indonesian government today continuously has tried to improve the quality of education by revising curriculum to all levels of education starting from elementary school to senior high school. The new implemented curriculum focus on the implementation of character which is integrated with all school subjects including mathematics. Character building at elementary level becomes main concern by all people because the main focus at elementary level is more on building good attitude rather than on knowledge and skill. This paper describes about on how to develop performance character and mathematics positively which includes confidence, positive view towards mathematics, improve students’ patience, improve student’s competence, praise for the student’s effort, develop student’s cleverness and gives motivation. By developing performance character and mathematics positivity could create an effective mathematics class, improve student’s behavior, avoid student’s constrain in learning mathematics and enhance student’s interest in learning mathematics.